Association of malnutrition with geriatric assessment impairments and health‐related quality of life among older adults with gastrointestinal malignancies. Issue 23 (4th September 2020) - Williams, Grant R.; Al‐Obaidi, Mustafa; Dai, Chen; Mir, Nabiel; Challa, Sai Alekha; Daniel, Michael; Patel, Harita; Barlow, Brett; Young‐Smith, Crystal; Gbolahan, Olumide; Paluri, Ravi; Bhatia, Smita; et al.
Abstract : Background: A majority of older adults with cancer develop malnutrition; however, the implications of malnutrition among this vulnerable population are poorly understood. The goal of this study was to quantify the prevalence of nutrition related‐symptoms and malnutrition among older adults with gastrointestinal (GI) malignancies and the association of malnutrition with geriatric assessment (GA) impairment, health‐related quality of life (HRQoL), and health care utilization. Methods: We performed a cross‐sectional study of older adults (≥60 years) who were referred to the GI Oncology clinic at the University of Alabama at Birmingham. Participants underwent the Cancer & Aging Resilience Evaluation survey that includes the abbreviated Patient‐Generated Subjective Global Assessment of nutrition. Nutrition scores were dichotomized into normal (0‐5) and malnourished (≥6), and multivariate analyses adjusted for demographics, cancer type, and cancer stage were used to examine associations with GA impairment, HRQoL, and health care utilization. Results: A total of 336 participants were included (men, 56.8%; women, 43.2%), with a mean age of 70 years (standard deviation, ±7.2 years) and colorectal cancer (33.6%) and pancreatic cancer (24.4%) being the most common diagnoses. Overall, 52.1% of participants were identified as malnourished. Malnutrition was associated with a higher prevalence of several GA impairments, including 1 or more falls (adjusted odds ratio [aOR], 2.1), instrumental activities of daily living impairment (aOR, 4.1), and frailty (aOR, 8.2). Malnutrition was also associated with impaired HRQoL domains; both physical (aOR, 8.7) and mental (aOR, 5.0), and prior hospitalizations (aOR, 2.2). Conclusion: We found a high prevalence of malnutrition among older adults with GI malignancies that was associated with increased GA impairments, reduced HRQoL, and increased health care utilization. Abstract : Over half (52.1%) of older adults with gastrointestinal malignancies are malnourished, with poor appetite and early satiety the most common nutrition‐related symptoms. Malnutrition is associated with a higher prevalence of several geriatric assessment impairments, including 1 or more falls, instrumental activities of daily living impairment, and frailty, as well as reduced health‐related quality of life and prior hospitalizations.